Design of H2/H∞ RMPC for Boiler Superheated Steam Temperature Based on Memoryless Feedback Multistep Strategy. (18th April 2017) - Han, Pu; Liu, Miao; Wang, Dongfeng; Jia, Hao
Abstract : The collection of superheated steam temperature models of a thermal power plant under different loads can be approximated to "multimodel" linear uncertain systems. After transformation, the tracking system was obtained from "multimodel" linear uncertain systems. For this tracking uncertain system, a mixed H 2 / H ∞ robust model predictive control (HRMPC) based on a memoryless feedback multistep strategy is proposed. A multistep control strategy combines the advantages of predictive control rolling optimization with memoryless feedback control thoughts. It could effectively decrease the controller optimization parameter and ensure closed-loop system stability, and, at the same time, it also achieved acceptable control performance. Successful application to the superheated steam temperature system of a 300 MW thermal power plant verified the study of the HRMPC-P cascade controller design scheme in terms of feasibility and effectiveness.